Theoretical and Methodological Foundations of the Study of the Archaization of Social Consciousness - Katrukha, Eugeny (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2018)
The article analyzes the theoretical approaches to the study of the archaization of public consciousness. The epistemological and ontological aspects of the problem is described in the context of Ukrainian society. The main theoretical propositions regarding the archaization of public consciousness in the concepts of D. Abdrahmanov, A. Ahiezer, V. Burlachuk, L. Ionin, A. Yakovenko, A. Soshnikov, C. Lamaja, A. Chirina, V. Fedotova, D. Novikov, A. Tishkov and other researchers have been reviewed and commented on. It is emphasized that the main factors of archaization are the crisis of social transformation and globalization processes. The authors definition of the archaization of public consciousness is given and its essential characteristics (primitivization, irrationalization, mythologization of consciousness) are singled out, an empirical interpretation of archaization is given. We formulated a hypothesis about the construction of the process of archaization by the authorities and the media.